European Consensus on Malabsorption-UEG & SIGE, LGA, SPG, SRGH, CGS, ESPCG, EAGEN, ESPEN, and ESPGHAN: Part 2: Screening, Special Populations, Nutritional Goals, Supportive Care, Primary Care Perspective - Lenti, Marco Vincenzo; Hammer, Heinz Florian; Tacheci, Ilja; Burgos, Rosa; Schneider, Stephane; Foteini, Anastasiou; Derovs, Aleksejs; Keller, Jutta; Broekaert, Ilse; Arvanitakis, Marianna; Dumitrascu, Dan Lucian; Segarra-Cantón, Oscar; et al. (United European gastroenterology journal, 2025)
Malabsorption is a complex and multifaceted condition characterised by the defective passage of nutrients into the blood and lymphatic streams. Several congenital or acquired disorders may cause either selective or global malabsorption in both children and adults, such as cystic fibrosis, exocrine pancreatic insufficiency (EPI), coeliac disease (CD) and other enteropathies, lactase deficiency, small intestinal bacterial overgrowth (SIBO), autoimmune atrophic gastritis, Crohn's disease, and gastric or small bowel resections. Early recognition of malabsorption is key for tailoring a proper diagnostic work-up for identifying the cause of malabsorption. Patient's medical and pharmacological history are essential for identifying risk factors. Several examinations like endoscopy with small intestinal biopsies, non-invasive functional tests, and radiologic imaging are useful in diagnosing malabsorption. Due to its high prevalence, CD should always be looked for in case of malabsorption with no other obvious explanations and in high-risk individuals. Nutritional support is key in management of patients with malabsorption; different options are available, including oral supplements, enteral or parenteral nutrition. In patients with short bowel syndrome, teduglutide proved effective in reducing the need for parenteral nutrition, thus improving the quality of life of these patients. Primary care physicians have a central role in early detection of malabsorption and should be involved into multidisciplinary teams for improving the overall management of these patients. In this European consensus, involving 10 scientific societies and several experts, we have dissected all the issues around malabsorption, including the definitions and diagnostic testing (Part 1), high-risk categories and special populations, nutritional assessment and management, and primary care perspective (Part 2).
Keywords: směrnice pro lékařskou praxi jako téma; Societies, Medical; Practice Guidelines as Topic; Gastroenterology; weight loss; Consensus; Europe; Nutritional Support; celiakie; konsensus; pancreatitis; Evropa; společnosti lékařské; Celiac Disease; dítě; Malabsorption Syndromes; Child; breath test; Mass Screening; primární zdravotní péče; Humans; diarrhoea; nutrition; malabsorpční syndromy; nutriční podpora; exokrinní pankreatická insuficience; gastroenterologie; plošný screening; coeliac disease; Primary Health Care; Exocrine Pancreatic Insufficiency; lidé; enteropathy